Iron tolerance of son-t rice varieties (Oryza sativa L.) commonly grown in Nigeria. - AJAYI , E.O.; ADEPETU, J.A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A green-house study was conducted to determine the Fe tolerance of six rice varieties commonly grown in Nigeria. The varieties were grown on a soil to which variable levels (0 - 150ppm) of Fe were applied as Fe-EDTA Increasing concentration of Fe up to 150ppm did not affect tiller number at 8 weeks after seeding. Similarly, plant height did not improve except for slight increases in the variety, FARO 17 up to 25ppm. [n of dry matter yield within the range of Fe applied, the order of tolerance of the varieties to Fe-deficiency was FARO 25> FARO 15> FARO 8 > FARO 11 > FARO 12 >FARO 17, while the order of resistance to Fe toxicity was FARO 15 > FARO-8 > FARO 12>FARO 17 > FARO 11 FARO 25. Therefore, FARO 15 should thrive very well over a wide range (high to low) of available soil Fe. FARO 8 would yield well on soils high in soluble Fe. which may be toxic to other varietics. FARO 17 and FARO 12 will require moderately high level of available Fe for optimum yield whereas a relatively low level of Fe will be required to give optimum yields in FARO 11 and FARO 25.